2012
DOI: 10.3109/02699052.2012.655360
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural symptoms 1 year after traumatic brain injury: A preliminary study of the relationship between race/ethnicity and symptoms

Abstract: Hispanics scored significantly higher than Whites and African Americans on the sub-scales of the NFI, indicating more problems in these areas. Future research should focus on identifying factors that may contribute to the difference between the groups and treatment interventions should be implemented accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Neurobehavioral symptoms are more likely to occur in the context of chronic emotional disruptions [e.g., depression (1215)] that are common in the general population and after TBI (16, 17). Symptom-reporting after injury may also differ based on age (18, 19), gender (20, 21), education (22), race or ethnicity (23), and injury severity (24, 25), though differences in symptom reporting by these personal factors are present in other clinical populations and the general population as well. A nationwide epidemiological study on TBI-related emergency department visits concluded that many of the common neurobehavioral symptoms after TBI may be more related to pre-existing psychiatric conditions (e.g., post-traumatic stress disorders, substance use disorders) and personality features (e.g., impulse control problems, high-risk behaviors) that put an individual at greater risk for sustaining a TBI, rather than to just the injury itself (17).…”
Section: Introductionmentioning
confidence: 99%
“…Neurobehavioral symptoms are more likely to occur in the context of chronic emotional disruptions [e.g., depression (1215)] that are common in the general population and after TBI (16, 17). Symptom-reporting after injury may also differ based on age (18, 19), gender (20, 21), education (22), race or ethnicity (23), and injury severity (24, 25), though differences in symptom reporting by these personal factors are present in other clinical populations and the general population as well. A nationwide epidemiological study on TBI-related emergency department visits concluded that many of the common neurobehavioral symptoms after TBI may be more related to pre-existing psychiatric conditions (e.g., post-traumatic stress disorders, substance use disorders) and personality features (e.g., impulse control problems, high-risk behaviors) that put an individual at greater risk for sustaining a TBI, rather than to just the injury itself (17).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Study design has been described previously. 16,17 In brief, inclusion criteria were severe, non-penetrating, traumatic brain injury requiring neurointensive care, with acute Glasgow Coma Scale score of [3][4][5][6][7][8]19 in adult patients aged 18-65 years. Exclusion criteria were death or expected death within 3 weeks of injury.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of terms have been used to describe these behavioural changes. [5][6][7][8][9] Descriptions in the literature pertaining to TBI include variations of "neurobehavioral symptoms", 5 "neuropsychatric consequences" 6 as well as standard definitions of psychiatric disorders (e.g. according to Diagnostic System Manual DSM 10 or International Classification of Disease ICD criteria), 11 applied to patients after traumatic brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Neurobehavioral symptoms, including aggression, disinhibition, lack of motivation, and difficulty planning/executing actions (1,2), are common after traumatic brain injury (TBI) and adversely affect participation and quality of life even many years after injury (3)(4)(5)(6)(7)(8)(9). Race and/or ethnicity (10), education (11), and gender (12,13) may also contribute to differences in neurobehavioral symptoms after TBI. Racial and ethnic minority groups report more psychiatric symptoms and cognitive deficits after TBI than non-Hispanic white individuals (10,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Race and/or ethnicity (10), education (11), and gender (12,13) may also contribute to differences in neurobehavioral symptoms after TBI. Racial and ethnic minority groups report more psychiatric symptoms and cognitive deficits after TBI than non-Hispanic white individuals (10,(14)(15)(16). Racial and ethnic minorities also experience healthcare disparities after brain injury (14,(16)(17)(18)(19)(20)(21)(22) that can magnify the long-term consequences of injury (14,(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%